PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT (STUDI KASUS DI KECAMATAN KARANGGAYAM, KEBUMEN) - Endah Tri Anomsari (NATAPRAJA, 2013)
This qualitative descriptive research aims to understand citizen participation in Community Based Forest Management (PHBM) case study in Karanggayam, Kebumen. Participation media consists of Lembaga Masyarakat Desa Hutan (LMDH), Communication Forum, Non-governmental organization, and others. Citizen participation in planning process is scarce in grass root level. Communication Forum is the media in which PHBM stakeholders can have deliberative dialogue but the forum is not implemented as expected. Meanwhile, people participate in PHBM implementation as they charge responsibility to manage and maintain forest safety. They also support the program by providing labors and cooperating with Perhutani such as making communal farm and making land rent contract. Citizen participation also includes sharing profit and benefits of PHBM. The obstacles of participation is ineffective stakeholders’ dialogue, dependent civil society, and Perhutani’s domination over other stakeholders. Keywords: citizen participation, PHBM.